2010
DOI: 10.1016/j.neuron.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rap2A by the Ubiquitin Ligase Nedd4-1 Controls Neurite Development

Abstract: Summary Nedd4-1 is a ‘Neuronal Precursor Cell Expressed and Developmentally Downregulated Protein’ and among the most abundant E3 ubiquitin ligases in mammalian neurons. In analyses of conventional and conditional Nedd4-1 deficient mice, we found that Nedd4-1 plays a critical role in dendrite formation. Nedd4-1, the serine/threonine kinase TNIK, and Rap2A form a complex that controls Nedd4-1-mediated ubiquitination of Rap2A. Ubiquitination by Nedd4-1 inhibits Rap2A function, which reduces the activity of Rap2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
146
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 62 publications
8
146
1
Order By: Relevance
“…A known (S381) and a predicted (S385) (34) proximal phosphorylation site on NEDD4-1 also occur within this binding domain. NEDD4-1, TNIK, and Rap2A are known to form a complex that regulates NEDD4-1-mediated Rap2A ubiquitination (35). Together, our findings suggest that cross-talk between phosphorylation and O-GlcNAcylation may be involved in the NEDD4-1/ TNIK/Rap2A (35) signaling pathway that regulates neurite growth.…”
Section: Known and Previously Unreported O-glcnacylated Proteins And mentioning
confidence: 59%
See 2 more Smart Citations
“…A known (S381) and a predicted (S385) (34) proximal phosphorylation site on NEDD4-1 also occur within this binding domain. NEDD4-1, TNIK, and Rap2A are known to form a complex that regulates NEDD4-1-mediated Rap2A ubiquitination (35). Together, our findings suggest that cross-talk between phosphorylation and O-GlcNAcylation may be involved in the NEDD4-1/ TNIK/Rap2A (35) signaling pathway that regulates neurite growth.…”
Section: Known and Previously Unreported O-glcnacylated Proteins And mentioning
confidence: 59%
“…Together, our findings suggest that cross-talk between phosphorylation and O-GlcNAcylation may be involved in the NEDD4-1/ TNIK/Rap2A (35) signaling pathway that regulates neurite growth. We also suggest that this cross-talk may extend to ubiquitination, given that TNIK is required in this complex to enable ubiquitination of Rap2A (35) and that its interaction with NEDD4-1 may be regulated by O-GlcNAcylation/phosphorylation.…”
Section: Known and Previously Unreported O-glcnacylated Proteins And mentioning
confidence: 85%
See 1 more Smart Citation
“…The Ras-subfamily GTPase Rap1B determines which of the initially formed neurites of a developing nerve cells becomes the axon by recruiting Cdc42 to the axonspecified neurite 91 ; Rap2 promotes the retraction of the other neurites 92 . Several recent studies demonstrated that direct ubiquitination of Rho and Ras subfamily small GTPases by HECT-type and RING finger-type E3 ligases regulates their expression level [93][94][95] , subcellular compartmentalization 13,96 , or function 97 ( Figure 5). …”
Section: Figure 5: Regulation Of Neuritogenesis By Ubiquitylation Amentioning
confidence: 99%
“…Consequently, the regulation of RhoA and Rap1B by Smurf-mediated ubiquitination and degradation is dependent on the activities of GAPs. In contrast to RhoA and Rap1B, which are targeted by Smurfs when in the GDP bound state, the active GTP-bound form of Rap2 is conjugated with a single ubiquitin (monoubiquitination) or a K63-linked diubiquitin moiety (diubiquitination) by Nedd4-1 97 . Rap2 ubiquitination by this mechanisms does not affect protein degradation but rather blocks the interactions of Rap2 with target proteins.…”
Section: Figure 5: Regulation Of Neuritogenesis By Ubiquitylation Amentioning
confidence: 99%